Peningkatan Pemahaman dan Praktik Filantropi Islam melalui Pengabdian kepada Masyarakat Bandar Selamat - Dalimunthe, Kariamin (Ibrah : Jurnal Pengabdian Kepada Masyarakat, 2023)
This community service aims to provide education on the management of philanthropy according to Islamic law. The objective is to benefit participants in understanding the practical aspects of managing household finances in accordance with Sharia, thereby contributing to the government's community empowerment programs. The research employs a qualitative approach, focusing on the understanding and behavioral changes within the community. Data is collected through direct engagement with sources during the implementation of the community service activities. The collection techniques include: 1) Interviews with key informants and participants, 2) Observations of activities, and 3) Documentation studies. The primary data sources are the informants and members of the "Traders' Mutual Aid Union Pajak Kuburan". Thematic analysis is applied to analyze the collected data. The research findings indicate: 1) Initial issues reveal that members of the "Traders' Pajak Kuburan Bandar Selamat Medan Tembung" still have limited understanding of Islamic philanthropy. 2) The chosen community service methods are: (a) Lecture method, (b) Tutorial method (Mentoring), and (c) Discussion method. The outcomes of this community service recommend the necessity of sustained programs to deepen the understanding of Islamic philanthropy and measure its implementation impact in daily life.